Difficulties that pre-service efl teachers have in lesson planning for young English language learners: a case study - Nguyễn, Lã Yến Nhi (2020)
Lesson planning is an essential skill that every teacher should practice and hone because of significant effects on lessons it brings back to teachers. However, planning for an effective lesson is challenging for teachers, especially pre-service teachers. This research investigated the pre-service EFL teachers‟ lesson planning practices to explore student teachers‟ awareness of their real difficulties in planning lessons for young learners. The research employed the framework of criteria for an effective lesson plan proposed by Strong and Xu (2016) to examine pre-service teachers‟ difficulties in formulating learning objectives, creating quality assignments and assessments, organizing the lessons, developing instructional strategies, timing, planning for differentiation and developmental appropriateness. In this case study, both qualitative and quantitative methods are used to form instruments and analyze collected data. Through an analysis of lesson plans created by three senior students and semi-constructed interviews, the research indicated that teacher candidates encountered obstacles in developing almost every part of a lesson plan. However, they did not manage to identify exactly and adequately their own problems as well as the quality of their performances on lesson planning. Finally, the research proposed some recommendations to heighten student teachers‟ self-awareness and enhance their planning competences.